2014
DOI: 10.1007/s10750-014-2067-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-native rainbow trout change the structure of benthic communities in headwater streams of the Cape Floristic Region, South Africa

Abstract: Introduced rainbow trout Oncorhynchus mykiss have invaded many headwater streams in the Cape Floristic Region (CFR) and depleted, or eliminated, native fish populations. However, the question of whether trout invasions also have consequences for lower trophic levels in these systems has not been addressed. We used a broad-scale comparative study in the upper Breede River catchment (CFR) to evaluate differences in benthic community structure between sites on headwater streams with and without trout, and thereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 59 publications
2
28
3
Order By: Relevance
“…Data on the feeding habits of Cape galaxias and Cape kurper are scarce, but available information suggests that both species feed primarily on benthic invertebrates (Skelton, 2001). Unexpectedly, redfin appeared to avoid grazer-scraper taxa which is inconsistent with the pattern described by Shelton et al (2014b). Our GCA results in the present study largely support the notion that redfin are stronger regulators of collectorgatherer taxa than are trout.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Data on the feeding habits of Cape galaxias and Cape kurper are scarce, but available information suggests that both species feed primarily on benthic invertebrates (Skelton, 2001). Unexpectedly, redfin appeared to avoid grazer-scraper taxa which is inconsistent with the pattern described by Shelton et al (2014b). Our GCA results in the present study largely support the notion that redfin are stronger regulators of collectorgatherer taxa than are trout.…”
Section: Discussioncontrasting
confidence: 67%
“…As our fish-collecting methods were not size-selective, and as the ranges of lengths of trout and redfin analysed in this study cover the range of sizes for these species found in CFR headwater streams (Shelton et al, 2014a), we consider our results to be representative of naturally occurring populations. While there were clear differences in food availability between streams with and without trout (Shelton et al, 2014b), the main difference was that aquatic invertebrate abundance in streams with trout was approximately twice that in streams with no trout. Because the focus of the present study was on characterising and comparing the feeding habits of redfin and trout in allopatry rather than in sympatry, differences in the availability of different food types among sites could potentially confound interspecific differences in gut content composition.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…There are two likely explanations for this decline in Niobrara River ecosystem health: the introductions of invasive northern pike (E. lucius) and yellow flag iris (Bowles et al, 2013;Spurgeon et al, 2014). Pike are piscivores and likely caused a decline in the resident fish assemblage from 11 to 3 species between 1989 and 2011 (Spurgeon et al, 2014) triggering a trophic cascade that affected the invertebrate assemblage in the river (Carpenteret al, 1987;Tronstad et al, 2010;Shelton et al, 2015;Wilmot et al, 2016). Furthermore, the invasion of non-native plants may have altered the stream ecosystem (Bowles et al, 2013;Spurgeon et al, 2014).…”
Section: Long-term Changes To the Niobrara River Ecosystemmentioning
confidence: 99%